De novo metatranscriptomic exploration of gene function in the millipede holobiont - Sardar, Puspendu; Šustr, Vladimír; Chroňáková, Alica; Lorenc, František; Faktorová, Lucie (Scientific reports, 2022)
Invertebrate-microbial associations are widespread in the biosphere and are often related to the function of novel genes, fitness advantages, and even speciation events. Despite ~ 13,000 species of millipedes identified across the world, millipedes and their gut microbiota are markedly understudied compared to other arthropods. Exploring the contribution of individual host-associated microbes is often challenging as many are uncultivable. In this study, we conducted metatranscriptomic profiling of different body segments of a millipede at the holobiont level. This is the first reported transcriptome assembly of a tropical millipede Telodeinopus aoutii (Demange, 1971), as well as the first study on any Myriapoda holobiont. High-throughput RNA sequencing revealed that Telodeinopus aoutii contained > 90% of the core Arthropoda genes. Proteobacteria, Bacteroidetes, Firmicutes, and Euryarchaeota represented dominant and functionally active phyla in the millipede gut, among which 97% of Bacteroidetes and 98% of Firmicutes were present exclusively in the hindgut. A total of 37,831 predicted protein-coding genes of millipede holobiont belonged to six enzyme classes. Around 35% of these proteins were produced by microbiota in the hindgut and 21% by the host in the midgut. Our results indicated that although major metabolic pathways operate at the holobiont level, the involvement of some host and microbial genes are mutually exclusive and microbes predominantly contribute to essential amino acid biosynthesis, short-chain fatty acid metabolism, and fermentation.
Keywords: střevní mikroflóra; Arthropods; esenciální aminokyseliny; kyseliny mastné těkavé; Animals; Gastrointestinal Microbiome; členovci; Amino Acids, Essential; Fatty Acids, Volatile; Bacteroidetes; zvířata